2021
DOI: 10.1080/10717544.2021.2012307
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of Agarwood extract-loaded nanocapsules and evaluation of their toxicity and anti-inflammatory activity on RAW 264.7 cells and in zebrafish embryos

Abstract: Aquilaria malaccensis has been traditionally used to treat several medical disorders including inflammation. However, the traditional claims of this plant as an anti-inflammatory agent has not been substantially evaluated using modern scientific techniques. The main objective of this study was to evaluate the anti-inflammatory effect of Aquilaria malacensis leaf extract (ALEX-M) and potentiate its activity through nano-encapsulation. The extract-loaded nanocapsules were fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 90 publications
0
5
0
2
Order By: Relevance
“…peaks of the AzA-TEs optimized formula and the plain drug free formula were identical, which confirms that AzA was successfully encapsulated in the nanovesicles [57].…”
Section: In Vitro Release Of Aza From the Optimized Formulamentioning
confidence: 53%
See 1 more Smart Citation
“…peaks of the AzA-TEs optimized formula and the plain drug free formula were identical, which confirms that AzA was successfully encapsulated in the nanovesicles [57].…”
Section: In Vitro Release Of Aza From the Optimized Formulamentioning
confidence: 53%
“…FTIR spectrum of AzA-TEs showed that the characteristic absorption peaks of AzA disappeared indicating the drug encapsulation within the nanovesicles. In addition, the peaks of the AzA-TEs optimized formula and the plain drug free formula were identical, which confirms that AzA was successfully encapsulated in the nanovesicles [ 57 ].…”
Section: Resultsmentioning
confidence: 87%
“…Os testes de toxicidade podem ser divididos em efeitos agudos e crônicos. Além da toxicidade, os potenciais efeitos antioxidantes e anti-inflamatórios foram as atividades mais investigadas dos produtos naturais em Zebrafish (PATEL et al, 2020;CERBARO et al, 2020;PIÑUEL et al, 2019;EISSA et al, 2021;LEE et al, 2017;VALLVERDÚ-QUERALT et al, 2015). Como elencado anteriormente o estresse oxidativo e a inflamação participam da fisiopatogênese de inúmeras doenças, paralelamente a isto, sabe-se que cerca de 70% dos genes humanos são encontrados no Zebrafish, fato que otimiza a mimetização de doenças e de processos que precedem doenças, como a inflamação e o estresse oxidativo.…”
Section: Atividade Biológica De Produtos Naturais Em Ensaios Pré-clín...unclassified
“…Como elencado anteriormente o estresse oxidativo e a inflamação participam da fisiopatogênese de inúmeras doenças, paralelamente a isto, sabe-se que cerca de 70% dos genes humanos são encontrados no Zebrafish, fato que otimiza a mimetização de doenças e de processos que precedem doenças, como a inflamação e o estresse oxidativo. Diante disto, a avaliação de biomoléculas envolvidas no estresse oxidativo [EROs; AGEs; MDA; 8-OHdG; NF-KB; além de enzimas antioxidantes -superóxido dismutase (SOD), catalase (CAT) e glutationa S-transferase (GST)] e na inflamação (IL-6; IL-1b), possuem valor quando investigadas em Zebrafish (EISSA et al, 2021).…”
Section: Atividade Biológica De Produtos Naturais Em Ensaios Pré-clín...unclassified
“…Studying the biological activity of A. sinensis leaf extract will help expand the plant’s therapeutic and medicinal potential and realize the comprehensive utilization of resources. The extracts from agarwood leaves exhibit a variety of biological activities, including antimicrobial, anticancer, and anti-inflammatory properties ( Cheng et al, 2013 ; Kamonwannasit et al, 2013 ; Eissa et al, 2021 ). Additionally, A. sinensis leaf extracts may help improve the immune response of macrophages by regulating pro-inflammatory cytokines and also enhance innate immunity against infection on RAW264.7 murine macrophages.…”
Section: Introductionmentioning
confidence: 99%